2022
DOI: 10.3390/biomedicines10061452
|View full text |Cite
|
Sign up to set email alerts
|

The Mediating Effect of Cytokines on the Association between Fungal Sensitization and Poor Clinical Outcome in Asthma

Abstract: Sensitization to fungal allergens is one of the proposed phenotypes in asthma. An association between fungal sensitization and worse clinical outcomes is apparent. Moreover, fungal sensitization in asthma that is associated with different type of immunological mechanism has been reported. How the role of cytokines mediates the association between fungal sensitization and poorer asthmatic outcomes remains unclear. We aimed to determine role of cytokines in the relationship between fungal sensitization and worse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…Recent studies documented the association between fungal sensitization and asthmatic severity. Lin et al reported that the connection between fungal sensitization and poorer clinical findings is evident [21]. While Kao et al added that fungal sensitization not only contributes to the development of asthma but also the severity of asthmatic condition [22].…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies documented the association between fungal sensitization and asthmatic severity. Lin et al reported that the connection between fungal sensitization and poorer clinical findings is evident [21]. While Kao et al added that fungal sensitization not only contributes to the development of asthma but also the severity of asthmatic condition [22].…”
Section: Discussionmentioning
confidence: 99%
“…Exposure to different environmental factors may affect different mechanisms and asthma progression. For example, IL-17A is a potential mediator to link Candida albicans sensitization and poor outcomes for asthma [ 127 ].…”
Section: Biomarkers Of Asthmamentioning
confidence: 99%